Embarkations - paglalakbay trajectories of flight (Philippines Cultural Studies Center, 2010)
Experimental video of multimedia rendering of poems, montages of scenes and landscapes, an other filmed happenings. Trajectories of flight from subaltern voyeur, Metro Manila visions and zen-scapes of the neocolonial and insurgent Philippine society of the spectacle.